Paper Tape Prevents Foot Blisters: A Randomized Prevention Trial Assessing Paper Tape in Endurance Distances II (Pre-TAPED II). Issue 5 (September 2016) - Lipman, Grant S.; Sharp, Louis J.; Christensen, Mark; Phillips, Caleb; DiTullio, Alexandra; Dalton, Andrew; Ng, Pearlly; Shangkuan, Jennifer; Shea, Katherine; Krabak, Brian J.
Abstract : Objective: To determine whether paper tape prevents foot blisters in multistage ultramarathon runners. Design: Multisite prospective randomized trial. Setting: The 2014 250-km (155-mile) 6-stage RacingThePlanet ultramarathons in Jordan, Gobi, Madagascar, and Atacama Deserts. Participants: One hundred twenty-eight participants were enrolled: 19 (15%) from the Jordan, 35 (27%) from Gobi, 21 (16%) from Madagascar, and 53 (41%) from the Atacama Desert. The mean age was 39.3 years (22-63) and body mass index was 24.2 kg/m 2 (17.4-35.1), with 31 (22.5%) females. Interventions: Paper tape was applied to a randomly selected foot before the race, either to participants' blister-prone areas or randomly selected location if there was no blister history, with untaped areas of the same foot used as the control. Main Outcome Measures: Development of a blister anywhere on the study foot. Results: One hundred six (83%) participants developed 117 blisters, with treatment success in 98 (77%) runners. Paper tape reduced blisters by 40% ( P < 0.01, 95% confidence interval, 28-52) with a number needed to treat of 1.31. Most of the study participants had 1 blister (78%), with most common locations on the toes (n = 58, 50%) and heel (n = 27, 23%), with 94 (80%) blisters occurring by the end of stage 2. Treatment success was associated with earlier stages [odds ratio (OR), 74.9, P < 0.01] and time spent running (OR, 0.66, P = 0.01). Conclusion: Paper tape was found to prevent both the incidence and frequency of foot blisters in runners.